2013
DOI: 10.1242/jcs.134510
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-specific expression of Fra-2/AP-1 controls Adiponectin/Osteocalcin expression and affects metabolism

Abstract: SummaryRecent studies have established that the skeleton functions as an endocrine organ affecting metabolism through the osteoblast-derived hormone osteocalcin (Ocn). However, it is not fully understood how many transcription factors expressed in osteoblasts regulate the endocrine function. Here, we show that mice with osteoblast-specific deletion of Fra-2 (Fosl2) have low bone mass but increased body weight. In contrast, transgenic expression of Fra-2 in osteoblasts leads to increased bone mass and decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 41 publications
(48 reference statements)
0
35
0
Order By: Relevance
“…Fra-2 Dep mice were generated by crossing Fra-2 f/f mice with mice expressing Cre recombinase from the K5 promoter (Zenz et al 2005). Control (Cre-negative mice), Fra Fra-2 Ep-tetOFF mice were generated by crossing mice carrying a Flag-tagged Fra-2 cDNA knock-in controlled by a tetracycline operator downstream from the col1a1 gene (col Fra-2 +/KI ) (Bozec et al 2013) to mice expressing tTA from the K5 promoter (Diamond et al 2000). ) were identified by genotyping PCR on tail biopsies.…”
Section: Micementioning
confidence: 99%
“…Fra-2 Dep mice were generated by crossing Fra-2 f/f mice with mice expressing Cre recombinase from the K5 promoter (Zenz et al 2005). Control (Cre-negative mice), Fra Fra-2 Ep-tetOFF mice were generated by crossing mice carrying a Flag-tagged Fra-2 cDNA knock-in controlled by a tetracycline operator downstream from the col1a1 gene (col Fra-2 +/KI ) (Bozec et al 2013) to mice expressing tTA from the K5 promoter (Diamond et al 2000). ) were identified by genotyping PCR on tail biopsies.…”
Section: Micementioning
confidence: 99%
“…The various FOS proteins play key roles in distinct developmental, physiological, and pathological processes [6], but these individual roles and the mechanisms involved are not yet clear. FOSL2 exerts a specific function in bone development [7] and appears to have selective physiological and pathological roles in diverse processes, including photoperiodic regulation [8], cancer [9], and fibrosis [10]. Several previous studies have indicated that FOSL2 plays a key role in the regulation of TGF-β pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The Fos gene family plays an important role in cell differentiation and proliferation [19]. Meanwhile, FOSL2 gene expression has been linked to fat metabolism, cancer, and bone diseases in human and animals [14, 2022]. …”
Section: Discussionmentioning
confidence: 99%
“…The Fos gene family is constituted by FOSL2, FOS, FOSB, and FOSI , and FOSL2 has been described in many different tissue types in both animals and humans [13]. Recent studies have found that it plays a crucial role in forming fat cells; meanwhile, some researchers have demonstrated that metabolism can be affected by FOSL2 expression [14, 15]. …”
Section: Introductionmentioning
confidence: 99%